Edukasi Pertolongan Pertama Pada Cedera Sejak Usia Dini - Pradnya, Matilda Stella; Setyaningsih, Mayang; Hartutik (Journal of Community Research and Service, 2025)
Children are vulnerable to unintentional injuries, such as lacerations, bruises, burns, nosebleeds, muscle strains,and so on. Home and school environments are the most common places where children get injuries. Injuries that are nottreated properly can cause infections and disabilities that affect children's daily functions. Children require education andtraining from a young age to improve their knowledge and awareness of protecting themselves and administering primarywound care. This community service activity was carried out at Marsudirini Elementary School, Gedangan, Semarangwith 52 participating students from grades 1, 2, and 3. The educational method was to provide material with a lecturemethod on the types and the dangers of injuries, as well as training and practice on handling various types of injuries.Evaluation of the activity was carried out by administering a pretest-posttest questionnaire. The results of this activityshowed an increase in students' knowledge at Marsudirini Elementary School, Gedangan, Semarang before and afterproviding education related to first aid for injuries.